Does institutional quality moderate the relationship between corporate governance and stock liquidity? Evidence from the emerging market of Pakistan - Ali, Shuaib; Zhongxin, Wu; Ali, Zahid; Fei, Guo; Chowdhury, Muhammad Abir Shahid (Frontiers in Psychology, 2022)
The prime aim of this study is to empirically analyse whether institutional quality moderates the relationship between corporate governance and stock liquidity? Through the light of agency and information asymmetry theory. To the best of our knowledge, this is the first finance study. The sample consists of non-financial firms listed on the Pakistan stock exchange during the period of 2009–2019. We use an instrumental variable approach and our new Institutional quality index composed of world governance indicators and corporate governance index, developed via principal component analysis, to demonstrate a relationship between corporate governance and stock liquidity and check the moderating role of institutional quality. Our results show a significant, positive relationship between the corporate governance index and stock liquidity, suggesting that well-governed firms have high liquidity. The results show that the institutional quality index has a positive moderating impact on the relationship between corporate governance and stock liquidity, suggesting that corporate governance in Pakistan is weak. Our results are robust to a series of endogeneity checks using alternative proxies of stock liquidity.